Changing Trends in Emergency Contraception - Roy, J; Chakraborty, Somajita (Nepal Journal of Obstetrics and Gynaecology, 2013)
Emergency contraception is defined as the use of drugs or devices to prevent pregnancy after unprotected coitus. It is sometimes referred to as ‘morning after’ or postcoital contraception. Global rates of unintended pregnancy are alarming and would suggest that knowledge of, and access to, emergency contraception is an area that needs to be developed1. Emergency contraception has been called the best-kept contraceptive secret. Emergency contraception provides a safe and effective means of postcoital contraception and has been estimated to prevent at least 75% of expected pregnancy resulting from unprotected intercourse. Previous research shows that several regimens of postcoital contraception offer safe and effective ways for women to avoid pregnancy. Yet the methods are often unavailable to women in developing countries. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 59-63 DOI: http://dx.doi.org/10.3126/njog.v7i1.8840